KEWENANGAN PEMERINTAH DAERAH DALAM MENYELESAIKAN SENGKETA PEMILIHAN KEPALA DESA SERENTAK: (Ditinjau dari Perda Kabupaten Lombok Timur Nomor 4 Tahun 2015 Tentang Tata Cara Pemilihan dan Pemberhentian Kepala Desa ) - ZULIYADI (Fakultas Hukum Universitas Gunung Rinjani, 2019)
The writing of this journal aims to determine the form of regional government responsibilities in resolving disputes over the selection of village heads simultaneously in 2016 in East Lombok Regency and to determine the pattern of dispute resolution for village head elections in 2016 by the Regional Government in East Lombok Regency, using normative juridical research methods, the results of this study are the form of responsibility carried out by the local government in resolving village head election disputes in East Lombok Regency, namely the Establishment of the Committee, the Establishment of a Level Supervisory Committee, the Establishment of the District Election Committee and the Formation of the Dispute Resolution Team for the Village Head Election in East Lombok Regency and the Pattern settlement of village head election disputes carried out by the Regional Government is the pattern of negotiation, mediation, conciliation through the implementation of deliberations by taking into account input from the village head election committee, BPD, Camat, and district level dispute resolution teams formed directly by the Regent through the East Lombok Regent letter.